Implementation of a Web-Based Accounting Information System for Cash Receipts and Disbursements Case Study: UD. Berkat Berkawan - Muhammad Bahit; Nadia Puteri Utami; Muhammad Zaki Ramadani (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The process of recording cash receipts and disbursements is an important part of financial management of an entity, be it a business, organization or individual. This process helps ensure that money received and disbursed is recorded correctly, so that it can be used to control finances, prepare financial reports, and fulfill tax obligations. The aim of this research is to create an accounting information system for cash receipts and disbursements at UD. Berkat Berkawan by creating a web-based cash receipt and disbursement application program. This research method uses a study method with an approach used to understand and analyze how an accounting information system operates in a business or organizational context. The results of this research can be used to facilitate UD. Berkat Berkawan in recording transactions and creating financial reports of cash receipts and disbursements. Keywords: Accounting Information Systems, Disbursements, Cash Receipts